A Review on Body Area Networks Security for Healthcare. (30th June 2011) - Zhang, Guang He; Poon, Carmen Chung Yan; Zhang, Yuan Ting
Abstract : Body area networks (BANs) are emerging as one of the main research trends in recent years, particularly in the area of personal health monitoring. Since health data are private and sensitive information, the security of data transmission within a BAN becomes a critical issue that requires immediate attention. In this paper, we attempt to examine possible attacks of the resource-constrained BANs and present state-of-the-art communication protocols, cryptographic methods, and key management schemes that are useful for BANs security. We will also discuss the problems of existing solutions and possible future research directions on security for BANs. A novel biometric method that utilizes the biological channels (biochannels) to assist secure information transmission within a BAN will also be highlighted and discussed.